Indole Aecetic Acid (IAA) Levels of Cladodes and Roots in Effect of Mycorrhizal and Actinorhizal Inoculation on C. equisetifolia under Glasshouse Condition - Raaman2, S. Elumalai1*, M. Prabhakaran1; N. (Recent Research in Science and Technology, 2011)
Casuarina equisetifolia is one of the economically important plant which will be used for firewood, medicinal property, N2 fixation, coastal environment preservation. In our present experiment carried out to find out the effect of mycorhizal and actinorhizal (Frankia) on C. equisetifolia on Indole Acitic Acid (IAA) level both cladodes and roots. The results recorded shows that the combined inoculated (VAM + Ectomycorhizal (Psilothus tinctorius) +Ã‚Â Actinorhizal (Frankia) enhancing the quality and quantity of IAA both in cladodes and roots, than the other individual treatments of symbionts. Since the C. equisetifolia is a tall plant longer height shoot, farmers can utilize this symbionts to the firewood production and N2 fixation.